COVID-19 surveillance systems in African countries - Yusuff Adebayo Adebisi; Adrian Rabe; Don Eliseo Lucero-Prisno III (Tabriz University of Medical Sciences, 2021)
Background: Surveillance forms the basis for response to disease outbreaks, including COVID-19. Herein, we identified the COVID-19 surveillance systems and the associated challenges in 13 African countries. Methods: We conducted a comprehensive narrative review of peer-reviewed literature published between January 2020 and April 2021 in PubMed, Medline, PubMed Central, and Google Scholar using predetermined search terms. Relevant studies from the search and other data sources on COVID-19 surveillance strategies and associated challenges in 13 African countries (Mauritius, Algeria, Nigeria, Angola, Cote d'Ivoire, the Democratic Republic of the Congo, Ghana, Ethiopia, South Africa, Kenya, Zambia, Tanzania, and Uganda) were identified and reviewed. Results: Our findings revealed that the selected African countries have ramped up COVID-19 surveillance ranging from immediate case notification, virological surveillance, hospital-based surveillance to mortality surveillance among others. Despite this, there exist variations in the level of implementation of the surveillance systems across countries. Integrated Disease Surveillance and Response (IDSR) strategy is also being leveraged in some African countries, but the implementation across countries remains uneven. Our study also revealed various challenges facing surveillance which included shortage of skilled human resources resulting in poor data management, weak health systems, complexities of ethical considerations, diagnostic insufficiency, the burden of co-epidemic surveillance, and geographical barriers, among others. Conclusion: With the variations in the level of implementation of COVID-19 surveillance strategies seen across countries, it is pertinent to ensure proper coordination of the surveillance activities in the African countries and address all the challenges facing COVID-19 surveillance using tailored strategies.